2018
DOI: 10.1002/ecs2.2491
|View full text |Cite
|
Sign up to set email alerts
|

Extinctions of interactions: quantifying a dung beetle–mammal network

Abstract: Loss of large‐bodied mammals across the globe through hunting, habitat degradation, and fragmentation is one of the most significant anthropogenic impacts on the environment. Cascading effects of these extinctions through ecosystems have been little studied, although correlative studies have revealed co‐extinctions in closely linked groups, with implications for ecosystem structure and function. Despite playing important roles in seed dispersal and hence seedling recruitment, mammals have been largely neglecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 86 publications
(162 reference statements)
0
42
0
Order By: Relevance
“…Yet a network approach is rarely attempted in studies of consumer-detritivore interactions. Studies on the ecological interactions between dung beetles and mammals suggest that the structure of dung beetle feeding and breeding networks did not differ significantly and showed high degree of nestedness and low levels of trophic specialization (Raine et al 2018, Raine andSlade 2019). On the other hand, the reintroduction of folivore primate (Alouatta guariba) in a previously defaunated Atlantic Forest site restored lost ecological interactions and promoted secondary seed dispersal, two years after the release of the first individuals (Genes et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Yet a network approach is rarely attempted in studies of consumer-detritivore interactions. Studies on the ecological interactions between dung beetles and mammals suggest that the structure of dung beetle feeding and breeding networks did not differ significantly and showed high degree of nestedness and low levels of trophic specialization (Raine et al 2018, Raine andSlade 2019). On the other hand, the reintroduction of folivore primate (Alouatta guariba) in a previously defaunated Atlantic Forest site restored lost ecological interactions and promoted secondary seed dispersal, two years after the release of the first individuals (Genes et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Model simulations have suggested that size-biased extinction scenarios for large mammals (and consequently the total amount and diversity of dung resources) will have detrimental effects on dung beetle populations (Raine et al 2018). The distribution of mammal body mass also influenced the size structure of dung beetle assemblages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations